Gout as a risk factor for acute myocardial infarction: evidence from competing risk model analysis. (17th May 2021) - Huang, Chia-Luen; Wang, Tai-Wen; Chen, Yong-Chen; Hu, Je-Ming; Ku, Po-Ming; Hsieh, Chang-Hsun; Lee, Chien-Hsing; Kuo, Feng-Chih; Lu, Chieh-Hua; Su, Cheng-Chiang; Liu, Jhih-Syuan; Lin, Fu-Huang; et al.
Abstract : Chronic inflammation, a hallmark of gout, is implicated in the pathogenesis of atherosclerosis. Thus, in theory, gout can be expected to increase the risk of acute myocardial infarction (AMI). Yet, results from several epidemiological studies have been inconclusive. A retrospective cohort study was conducted using the National Health Insurance Research Database of Taiwan dated from 2000 to 2013. The study cohort comprised 3581 patients with gout (the gout cohort) and 14, 324 patients without gout (the non-gout cohort). The primary outcome was the incidence of AMI. To estimate the effect of gout on the risk of AMI, the Lunn-McNeil competing risk model was fitted to estimate cause-specific hazard ratios (HRs) and their 95% confidence intervals (CIs). The cumulative incidence of AMI was significantly higher in the gout cohort than in the non-gout cohort, resulting in an adjusted HR of 1.36 (95% CI 1.04 to 2.76). Further, HRs of gout with incident AMI were higher in patients without hypertension, diabetes mellitus, or hyperlipidemia (ranging from 1.63 to 2.09) than in those with each of these comorbidities (ranging from 0.95 to 1.13). The results of this study suggest that patients with gout have an increased risk of AMI. The AMI risk associated with gout was conditional on patients' cardiovascular risk profile. Future work is needed to confirm these findings.